Preface: Proceedings of the 1st Symposium on Energy Efficiency in Buildings and Industry - Sergio Croquer; Junior Lagrandeur; Sébastien Poncet; Hachimi Fellouah (Proceedings, 2019)
Symposium on Energy Efficiency in Buildings and Industry. [...]